Immune Status of Children with Intestinal Infections Caused by Opportunistic Microorganisms on the Background of H.pylori Infection - T.A. Kirsanova (Zaslavsky O.Yu., 2015)
The article presents the results of studying immune status in children with intestinal infections caused by opportunistic pathogens followed by H.pylori infection. It is proved that in the acute phase of the disease, patients with H.pylori infection have increased levels of cytokines and B-lymphocytes, decrease of T-lymphocytes and local immunity factors, indicators of immunoglobulins remain within the physiological range. In early convalescence period we have noted in patients a slight increase in T-lymphocytes level, reduced level of cytokines, however, all figures are significantly different from that of healthy children; levels of immunoglobulin and local immunity factors remain within parameters of the acute period. In patients with H.pylori infection, functioning of immune system goes by hypocompensatory type. These data theoretically justify immunocorrecting therapy in this group of patients. Given more torpid normalization of immunity indicators in patients with H.pylori infection, in order to facilitate the evaluation of completeness of patients' recovery before discharge from hospital, it is recommended to study immunity parameters, and maintenance of their changes can be used to justify the expansion of the scope of rehabilitation measures at the stages of clinical supervision for convalescents.